2013
DOI: 10.1183/09031936.00104612
|View full text |Cite
|
Sign up to set email alerts
|

Macitentan for the treatment of idiopathic pulmonary fibrosis: the randomised controlled MUSIC trial

Abstract: Idiopathic pulmonary fibrosis is a progressive, fatal disease. This prospective, randomised, double-blind, multicentre, parallel-group, placebo-controlled phase II trial (NCT00903331) investigated the efficacy and safety of the endothelin receptor antagonist macitentan in idiopathic pulmonary fibrosis.Eligible subjects were adults with idiopathic pulmonary fibrosis of ,3 years duration and a histological pattern of usual interstitial pneumonia on surgical lung biopsy. The primary objective was to demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(164 citation statements)
references
References 34 publications
2
151
1
10
Order By: Relevance
“…Bosentan was found to be nonefficacious in two large placebo-controlled IPF trials [78,79] and in another large placebo-controlled evaluation in IPF, ambrisentan was associated with increased risk of disease progression and respiratory hospitalisations [80]. A recent trial of macitentan in IPF was also unsuccessful [81]. Taken together, these data provide no support for an antifibrotic interstitial effect of these therapies, despite supportive pre-clinical data.…”
Section: Treatmentmentioning
confidence: 98%
“…Bosentan was found to be nonefficacious in two large placebo-controlled IPF trials [78,79] and in another large placebo-controlled evaluation in IPF, ambrisentan was associated with increased risk of disease progression and respiratory hospitalisations [80]. A recent trial of macitentan in IPF was also unsuccessful [81]. Taken together, these data provide no support for an antifibrotic interstitial effect of these therapies, despite supportive pre-clinical data.…”
Section: Treatmentmentioning
confidence: 98%
“…versus placebo in pulmonary hypertension due to IPF was discontinued prematurely due to increased rates of death and serious adverse effects in the riociguat study arm. Negative randomised trial results have already been reported in IPF for nonselective (bosentan [80]) and selective (ambrisentan [81], macitentan [82]) endothelin receptor antagonists. Ambrisentan has actually been contraindicated in IPF patients, regardless of the presence of pulmonary hypertension, due to its association with increased rate of disease progression and respiratory hospitalisation [81].…”
Section: Therapymentioning
confidence: 99%
“…Another negative study was published by Rhagu et al, who investigated the effect of macitentan in IPF patients (Music Trial) [59]. The primary endpoint (FVC change) was not achieved.…”
Section: Treatment Considerations Of Ph In the Course Of Dpldsmentioning
confidence: 99%